Cdk6 contributes to cytoskeletal stability in erythroid cells - Uras, Iris Z.; Altamura, Sandro; Neves, Joana; Muckenthaler, Martina (Haematologica, 2017)
Mice lacking Cdk6 kinase activity suffer from mild anemia accompanied by elevated numbers of Ter119+ cells in the bone marrow. The animals show hardly any alterations in erythroid development, indicating that Cdk6 is not required for proliferation and maturation of erythroid cells. There is also no difference in stress erythropoiesis following hemolysis in vivo. However, Cdk6−/− erythrocytes have a shortened lifespan and are more sensitive to mechanical stress in vitro, suggesting differences in cytoskeletal architecture. Erythroblasts contain both Cdk4 and Cdk6, while mature erythrocytes apparently lack Cdk4 and their Cdk6 is partly associated with the cytoskeleton. We used mass spectrometry to show that Cdk6 interacts with a number of proteins involved in cytoskeleton organization. Cdk6−/− erythroblasts show impaired F-actin formation and lower levels of gelsolin, which interacts with Cdk6. We also found that Cdk6 regulates the transcription of a panel of genes involved in actin (de-)polymerization. Cdk6-deficient cells are sensitive to drugs that interfere with the cytoskeleton, suggesting that our findings are relevant to the treatment of patients with anemia - and may be relevant to cancer patients treated with the new generation of CDK6 inhibitors.
Pre-published: March 2, 2017
Gesehen am 09.10.2018